Single typical trichoscopic feature predictive of tinea capitis. (1st November 2019) - Dhaille, F.; Dillies, A.‐S.; Dessirier, F.; Reygagne, P.; Diouf, M.; Balthazard, T.; Lombart, F.; Hébert, V.; Chopinnaud, M.; Verneuil, L.; Becquart, C.; Delaporte, E.; et al.
Summary: This study which was carried out in four university hospitals in France was designed to assess the usefulness of the technique, trichoscopy, in the diagnosis of tinea capitis, also known as scalp ringworm. Tinea capitis is an infection of the scalp hair and the surrounding skin with a fungus. Fungi are microscopic organisms that can live on the hair, nails, and outer skin layer. It is common in children and the main treatment is a course of antifungal drugs taken by mouth. Currently tinea capitis is diagnosed by culture (taking samples and growing the fungi in a lab) or genetic analysis of the hair. Trichoscopy is a form of microscopic examination using a hand‐held magnifier called a dermatoscope, which allows someone trained in its use to see minute differences in the growth and shape of hairs. The study was carried out by dermatology trainees with an expert assessor who also examined the patients. The results found that trichoscopy showed a number of visible changes in infected hairs, each named for a specific identifiable feature e.g. corkscrew hairs or morse code hairs. The presence of just one of these changes was found to be an accurate predictor of infection, which was subsequently confirmed by the laboratory. These results suggest that this simple observational technique can be used to diagnose tinea capitis with accuracy. Furthermore, some of the visible changes are specific to particular fungi. This helps the dermatologist in selecting the correct treatment with antifungal medicines, which is different for different organisms. Abstract : Linked Article:  Dhaille et al. Br J Dermatol 2019; 181 :1046–1051